Characterisation and nucleation kinetics of carbamazepinesaccharin co-crystal - Khairool Azizul, Mohammad (2020)
Carbamazepine (CBZ) has five different polymorphs and is a drug used to treat epilepsy. Major issue with CBZ is its low absorption and dissolution rate, thus high dosage is required for the effectiveness of the drug via oral route. Aiming to enhance the physicochemical properties of the drug, co-crystals of CBZ with relevant co-former, saccharin (SAC) is introduced. To date, the kinetics of CBZ-SAC co-crystals has been poorly characterised. The novelty of this research presents the application of different SAC/CBZ molar ratios (1.0, 2.0, 2.5, 3.0 and 3.5) at different CBZ concentrations to deduce the kinetic parameters via polythermal method at different cooling rates. The optimum condition of the production of CBZ-SAC co-crystals were found to be as SAC/CBZ mole ratio of 2.0 at a CBZ concentration of 17.96 mg/ml. The nucleation orders obtained from slow cooling method were in between 1.65 and 4.9, which were within the range for nucleation of organic compounds. Based on the results of kinetic study from the slow cooling method, a fast cooling experiment was conducted to evaluate the induction time, the radius of the critical nucleus and interfacial energy of the co crystal. The results from Kashchiev–Borissova–Hammond–Roberts (KBHR) method in determining the kinetic values of CBZ–SAC co-crystals were similar to those of the isothermal method. The effect of seed loading, seed size and the temperature of supersaturated solution at the time of seeding on the CBZ-SAC co-crystals were investigated. It was found that nucleation occurred faster when seeding is close to the super solubility curve (27.84 oC) which is at the highest supersaturation. The analysis of crystal size distribution (CSD) showed more fine particles were formed at a lower seeding temperature. On the other hand, nucleation occurred slower when seeding is close to the solubility curve (47.55 oC), which is at low supersaturation and therefore resulted in a smaller number of fine particles formed. The size of CBZ-SAC co-crystals formed from CSD analysis was in a range of 100 to 200 µm. Characterisation using Differential Scanning Calorimetry (DSC) and X-Ray Diffraction (XRD) of all CBZ-SAC co-crystal has proven that, the stable CBZ-SAC co-crystals of Form I were formed.